Developing an Analytical Framework to Discern Historical Developments in Physiotherapy - Cameron W. MacDonald; Robert Parkes; Peter G. Osmotherly (Archives of Medicine and Health Sciences)
An appreciation of the history of physiotherapy permits an understanding of the development of the profession and appreciates its societal role. However, the study of history within physiotherapy is confounded by methods favoring a deductive approach and the exclusion of bias. To discover the historical elements of a profession or a technique, methods applied in research need to be abductive, inclusive of bias, and open to alternative sources of information enabling the discovery and emplotment of new narratives. There is minimal attention to the historical development of the physiotherapy profession or the genesis of techniques utilized. Research methodologies used by those seeking to expand understanding are limited by the scientific health-care research methods chosen. This paper discusses a hybrid approach for historical research in our profession, using the example of an analytical framework to address the question of the historical genesis of manual therapy in health care, outlining the development of this method and including the creation of a novel historical source appraisal tool, as we seek to emplot an updated historical narrative.